Structural Insights of Shigella Translocator IpaB and Its Chaperone IpgC in Solution - Ferrari, Mariana L.; Charova, Spyridoula N.; Sansonetti, Philippe J.; Mylonas, Efstratios; Gazi, Anastasia D. (Frontiers in Cellular and Infection Microbiology, 2021)
Bacterial Type III Secretion Systems (T3SSs) are specialized multicomponent nanomachines that mediate the transport of proteins either to extracellular locations or deliver Type III Secretion effectors directly into eukaryotic host cell cytoplasm. Shigella, the causing agent of bacillary dysentery or shigellosis, bears a set of T3SS proteins termed translocators that form a pore in the host cell membrane. IpaB, the major translocator of the system, is a key factor in promoting Shigella pathogenicity. Prior to secretion, IpaB is maintained inside the bacterial cytoplasm in a secretion competent folding state thanks to its cognate chaperone IpgC. IpgC couples T3SS activation to transcription of effector genes through its binding to MxiE, probably after the delivery of IpaB to the secretion export gate. Small Angle X-ray Scattering experiments and modeling reveal that IpgC is found in different oligomeric states in solution, as it forms a stable heterodimer with full-length IpaB in contrast to an aggregation-prone homodimer in the absence of the translocator. These results support a stoichiometry of interaction 1:1 in the IpgC/IpaB complex and the multi-functional nature of IpgC under different T3SS states.